Twelve weeks of a diet and exercise intervention alters the acute bone response to exercise in adolescent females with overweight/obesity - Kurgan, Nigel; Skelly, Lauren E.; Ludwa, Izabella A.; Klentrou, Panagiota; Josse, Andrea R. (Frontiers in Physiology, 2023)
Exercise and consumption of dairy foods have been shown to improve bone mineralization. However, little is known about the magnitude and timing of their synergistic effects on markers and regulators of bone metabolism in response to acute exercise in adolescent females with obesity, a population susceptible to altered bone metabolism and mineral properties. This study examined the influence of twelve weeks of exercise training on the bone biochemical marker response to acute exercise and whether higher dairy consumption could further influence the response. Thirty adolescent females (14.3±2.0 years) with overweight/obesity (OW/OB) completed a 12-week lifestyle modification intervention involving exercise training and nutritional counselling. Participants were randomized into two groups: higher dairy intake (RDa; 4 servings/day; n=14) or low dairy intake (LDa; 0-2 servings/d; n=16). Participants performed one bout of plyometric exercise (5 circuits; 120 jumps) both pre- and post-intervention. Blood samples were taken at rest, 5 min and 1h post-exercise. Serum sclerostin, osteocalcin (OC), osteoprotegerin (OPG), receptor activator nuclear factor kappa B ligand (RANKL), and C-terminal telopeptide of type 1 collagen (βCTX) concentrations were measured. While there was an overall increase in sclerostin pre-intervention from pre to 5 min post-exercise (+11% p = 0.04), this response was significantly decreased post-intervention (-25%, p = 0.03) independent of dairy intake. The OPG:RANKL ratio was unresponsive to acute exercise pre-intervention but increased 1h post-exercise (+2.6 AU; p<0.001) post-intervention. Dairy intake did not further influence these absolute responses. However, after the 12-week intervention, the RDa group showed a decrease in the relative RANKL post-exercise response (-21.9%; p<0.01), leading to a consistent increase in the relative OPG:RANKL ratio response, which was not the case in the LDa group. There was no influence of the intervention or dairy product intake on OC, OPG, or βCTX responses to acute exercise (p>0.05). In conclusion, a lifestyle modification intervention involving exercise training blunts the increase in sclerostin and can augment the increase in OPG:RANKL ratio to acute exercise in adolescent females with OW/OB, while dairy product consumption did not further influence these responses.